KONSEP IDEOLOGI POLITIK DALAM AL-QUR‘AN - Masyhuri, Ahmad Ari (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
The political ideology in the Qur'an is a set of ideologies that believe that Islam should be a guideline for all aspects of human life, social, economic, political, cultural, and personal life. Also, the political ideology in the Qur'an can be seen from the basic principles that guide the development of a political system. The basic principles mentioned above include the obligation to realize the unity and integrity of the ummah, the obligation to hold deliberations in resolving problems, the obligation to carry out mandates and establish laws fairly, the obligation to obey Allah and the Prophet and Ulil Amri, resolving conflicts, maintaining state sovereignty, the obligation to prioritize peace rather than hostility, the obligation to increase vigilance in the field of defense and security, and the obligation to keep promises. This research method uses a qualitative type of literature review research. Sources of data are taken from literature reviews such as; relevant journals, books and references. The results of the study state that interactions that have religious connections and state ideology can strengthen the life of the nation and state in the form of creating an attitude of community tolerance, creating harmony, unity and unity and helping each other. The interaction of Pancasila ideology in the universal values of political ideology in the Qur'an can be studied in the five Pancasila precepts, namely Belief in One Almighty God, Just and Civilized Humanity, Indonesian Unity, Democracy Led by Wisdom in Deliberation/representation, and Justice. Social Services for All Indonesian People, is a reflection of the verses in the Al-Qur'an, that Pancasila is a political sub-ideology and the embodiment of Islamic teachings that originate from the Al-Qur'an.